Mini-implant and Modified Nance Button Assisted Alignment of a Horizontally Impacted Maxillary Canine - A Case Report - Dip Jyoti Baruah; Aravind Marikenchannanavar; Sujala Ganapati Durgekar (Galenos Yayinevi, 2021)
Orthodontic alignment of a horizontally impacted canine placed high and deep in the maxilla represents a challenging clinical scenario. This article describes a case report of a 16-year-old postpubertal male patient who was concerned about an unesthetic smile. The clinical and radiographic investigations revealed that the patient had retained deciduous canines and bilaterally impacted maxillary canines. The right impacted canine had a good prognosis. The left canine was horizontally impacted in the labial side with a Kau-Pan-Gallerano index score of 19, which indicates a "difficult" degree of treatment. The initial treatment plan was application of distal traction to the impacted left canine from reinforced anchorage unit to change its inclination from horizontal to vertical before erupting it toward occlusion. In this case report, we demonstrated the use of a mini-implant and a modified Nance button-assisted forced eruption of an impacted canine. The 12-month follow-up review showed that the results were maintained during the time, and the previously impacted teeth showed intact gingival attachments. A conservative surgical exposure of the impacted canine and well-planned biomechanics helped us achieve a desirable, esthetic outcome.